On Simmel’s Financial Aristocrat: from The Philosophy of Money to its Contemporary Actualisation - Cocozza, Donato (Simmel Studies, 2022)
Despite Simmel’s idea of a secondary qualitative significance of money, the paradigmatic figure of the “financial aristocrat” (Geldaristokrat), owner of a great amount of money, is conditioned by the external reality, the technical intellectualisation and the quantitative reduction of life contents. The problematic nature of such an expression lies in the fact that Simmel, like Nietzsche, sees a strong opposition between money culture (Geldkultur) and the aristocratic ideal (Vornehmheitsideal). However, such an expression seems rather fitting to the contemporary phenomenon of the emergency of cryptocurrencies, that can be considered as the actualisation of Simmel’s “perfect money”. Thus, it is hypothesised an aristocratic-cosmopolitan consideration of the miners as guarantors of perfectly desubstantialised money where the connection between money and technology comes to a hybridisation. Starting from these considerations and taking into account the importance of the financial aristocrat in Simmel’s framework, a phenomenological observation of the XXI century Geldkultur could be put forward..